IMPLEMENTASI KERJASAMA INDONESIA - RUSIA TERKAIT RADIO Republik Indonesia DAN SPUTNIK NEWS AGENCY AND RADIO DALAM PERTUKARAN INFORMASI PERIODE 2017 - 2019 - Dara Mutiara, (2020)
This study discusses about the implementation cooperation of the Republic of Indonesia radio and Russian radio techniques related to radio as an information media during 2017-2018. Associated with communication for communication between countries and to create a more directed flow of information. The researcher uses one concept and one theory that are related to each other, namely the concept of new media and the theory of international cooperation. The research method uses descriptive qualitative, exploratory and analytical methods that help extract information and data about the cooperation of the Republic of Indonesia radio and Russian radio techniques related to radio as a medium of information transportation. In 2017, the agreement of cooperation between the two parties to clarify the bilateral relationship. The results showed that the relationship between the two parties was increasingly focused with the collaboration. Therefore, it is important for Indonesia to extend the future of this collaboration again so that Indonesia's image in the world will increase.